Mapping exercise and status update of eight established registries within the TREatment of ATopic eczema Registry Taskforce. (10th September 2022) - Bosma, Angela L.; Musters, Annelie H.; Bloem, Manja; Gerbens, Louise A. A.; Middelkamp‐Hup, Maritza A.; Haufe, Eva; Schmitt, Jochen; Barbarot, Sebastien; Seneschal, Julien; Staumont‐Sallé, Delphine; Johansson, Emma K.; Bradley, Maria; et al.
Abstract: Background: The TREatment of ATopic eczema (TREAT) Registry Taskforce is a collaborative international network of registries collecting data of atopic eczema (AE) patients receiving systemic and phototherapy with the common goal to provide long‐term real‐world data on the effectiveness, safety and cost‐effectiveness of therapies. A core dataset, consisting of domains and domain items with corresponding measurement instruments, has been developed to harmonize data collection. Objectives: We aimed to give an overview of the status and characteristics of the eight established TREAT registries, and to perform a mapping exercise to examine the degree of overlap and pooling ability between the national registry datasets. This will allow us to determine which research questions can be answered in the future by pooling data. Methods: All eight registries were asked to share their dataset and information on the current status and characteristics. The overlap between the core dataset and each registry dataset was identified (according to the domains, domain items and measurement instruments of the TREAT core dataset). Results and conclusions: A total of 4702 participants have been recruited in the eight registries as of 1st of May 2022. Of the 69 core dataset domain items, data pooling was possible for 69 domain item outcomes in TREAT NL (the Netherlands), 61 items in A‐STAR (UK and Ireland), 38 items in TREATgermany (Germany), 36 items in FIRST (France), 33 items in AtopyReg (Italy), 29 items in Biobadatop (Spain), 28 items in SCRATCH (Denmark) and 20 items in SwedAD (Sweden). Pooled analyses across all registries can be performed on multiple important domain items, covering the main aims of analysing data on the (cost‐)effectiveness and safety of AE therapies. These results will facilitate future comparative or joint analyses.